Leishmaniasis in immunosuppressed individuals. (20th February 2014) - van, J.; Carrillo, E.; López‐Vélez, R.; Lynen, L.; Moreno, J.
Abstract Leishmaniasis is a vector‐born chronic infectious disease caused by a group of protozoan parasites of the genus Leishmania. Whereas most immunocompetent individuals will not develop disease after Leishmania infection, immunosuppression is a well‐established risk factor for disease. The most severe form is visceral leishmaniasis (VL), which is typically fatal if untreated. Whereas human immunodeficiency virus (HIV) co‐infection (VL–HIV) was initially mainly reported from southern Europe, it is now emerging in other regions, including East Africa, India, and Brazil. VL has also been found in a wide range of non‐HIV‐related immunosuppressive states, mainly falling under the realm of transplantation medicine, rheumatology, haematology, and oncology. Clinical presentation can be atypical in immunosuppressed individuals, being easily misdiagnosed or mistaken as a flare‐up of the underlying disease. The best diagnostic approach is the combination of parasitological and serological or molecular methods. Liposomal amphotericin B is the drug of choice. Treatment failure and relapse rates are particularly high in cases of HIV co‐infection, despite initiation of antiretroviral treatment. Primary prophylaxis is not recommended, but secondary prophylaxis is recommended when the patient is immunosuppressed. Cutaneous leishmaniasis can have a number of particular features in individuals with immunosuppression, especially if severe, including parasite dissemination, clinical polymorphism with atypical and often more severe clinical forms, and even visceralization. Mucosal leishmaniasis is more common. Treatment of cutaneous and mucosal leishmaniasis can be challenging, and systemic treatment is more often indicated. With globally increased travel and access to advanced medical care in developing countries, the leishmaniasis burden in immunosuppressed individuals will probably continue to rise, warranting increased awareness and enhanced surveillance systems.